Geochemical properties of snow on the areas influenced by falling parts of the rocket carriers (Yakutia) - V. N. Makarov; L. S. Volkova (Лëд и снег)
Results of ecological and geochemical study of snow cover on the areas of the fall of the separating parts of the launch vehicles Soyuz-2 are discussed. The territories are the Aldan and Vilyuysky districts of Yakutia. The state of the environment was investigated at the sites in both situations, i.e. before the launch and after the fall of the separating parts of the rocket carriers. The background chemical composition of the snow cover in these regions is hydrocarbonate and ultra-fresh with low concentrations of trace elements. After the launch and fall of the rocket stages, the total chemical composition of snow remained bicarbonate, but the content of the elements P, Fe, Sr, Pb and phenols increased on the territory of the Aldan district, while in the Vilyuysky districts increasing elements were Fe, Sr, Pb, Li, Al, Mn and phenols. Pollution of the snow cover with metals and organic compounds was revealed directly under the fragments of the rocket stages, however occurrence of this contamination was limited to the radius of influence no longer 100 m. The larger low-contrast technogenic anomalies were related to Pb and phenols. The qualitative and quantitative characteristics of technogenic anomalies did rapidly reduce with distance from fragments of the rocket carriers. When snow melts, the main part of the pollutants flows down over the frozen ground to the water streams and bodies, and that is why no contrasting technogenic lithochemical anomalies were found in the soils under the fragments. Thus, our results demonstrate that the negative environmental impact on the environment in the areas of falling fragments of the Soyuz-2 carrier is limited to boundaries of the local territory and does not present any significant hazard to the environment and the health of population.